A Theory of Everything: Overlapping Neurobiological Mechanisms of Psychotherapies of Fear and Anxiety Related Disorders - Javanbakht, Arash (Frontiers in Behavioral Neuroscience, 2019)
Similarities within the phenomenology, neurobiology, psychotherapeutic, and pharmacological treatments of distinctly categorized anxiety and fear related disorders suggest the involvement of common neurobiological mechanisms in their formation. This theory of integration is the focus of the Research Domain Criteria (RDoC) approach initiated by the NIH. The current article explores potential facets of overlap among mainstream methods of psychotherapy for anxiety, fear, and trauma related disorders. These overlaps include associative learning of safety, cognitive reappraisal and emotion regulation, therapist as a social safety cue, and contextualization. Temporal contextualization and placing memories in their time and place will be suggested as a potentially important, and less explored aspect of psychotherapy.